Duality in multiobjective fractional programming problemswith strong pseudoinvexity constraints - Kanniappan, P.; Pandian, P. (Universiti Kebangsaan Malaysia, 2000)
A parametric approach is used to obtain necessary and suffient conditions for feasible point to be a properly efficient solution and duality results are established for multiobjective fractional programming problems with strong pseudoinvexity constraints.